2A Peptide-based, Lentivirus-mediated Anti-death Receptor 5 Chimeric Antibody Expression Prevents Tumor Growth in Nude Mice - Li, Meng (Nature Publishing Group, 2012)
Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), a member of the TNF superfamily, induces tumor cell death via death receptors on target cells, without adverse effects on most normal cells. Its receptors are therefore an attractive target for antibody-mediated tumor therapy. Here, we report the creation of a lentivirus vector constructed by linking the heavy chain and the light chain of the antibody with a 2A/furin self-processing peptide in a single open reading frame that expresses a novel chimeric antibody (named as zaptuximab) with tumoricidal activity, which is consisted of the variable region of a mouse anti-human DR5 monoclonal antibody, AD5-10, and the constant region of human immunoglobulin G1. Lentivirus-expressed zaptuximab bound specifically to its antigen, DR5, and exhibited significant apoptosis-inducing activity in various tumor cell lines. The packaged recombinant virus lenti-HF2AL showed strong apoptosis-inducing activity in vitro. Meanwhile, inoculated subcutaneous human colon HCT116 tumor formation in nude mice were inhibited significantly. Moreover, there was a synergistic effect of mitomycin C (MMC) on the observed tumoricidal efficacy, prolonging the life span of nude mice with orthotopic human lung tumor cancers. These data suggest that lentivirus-mediated, 2A peptide-based anti-DR5 chimeric antibody expression may have clinical utility as an anticancer treatment and may represent a rational adjuvant therapy in combination with chemotherapy.